Respuestas

2013-06-01T19:45:34+02:00
Desarrollo:
(2x^2,3y^2) = (-2+5x,5-14y)
como vemos tenemos que igualar:
2x^2=-2+5x  ....(1)    
3y^2=5-14y .....(2)
efectuamos la primera:
2x^2=-2+5x
2x^2-5x+2=0        (Aspa simple)
2x    ¡    -1      -x 
x      ¡    -2      -4x
         - - - - - - -5x
(2x-1)(x-2)=0
por tanto:
2x-1=0     x-2=0
x=1/2       x=2
efectuamos la segunda:
3y^2=5-14y
3y^2+14y-5=0        (Aspa simple)
3y    ¡     -1      -y 
y      ¡    +5     15y
         - - - - - - 14y
(3y-1)(y+5)=0
por tanto:
3y-1=0     y+5=0
y=1/3       y=-5

un gusto =D